2018
DOI: 10.1186/s12906-018-2240-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum ferritin as a prognostic factor in advanced hepatobiliary cancer patients treated with Korean medicine: a retrospective cohort study

Abstract: BackgroundAdvanced hepatobiliary cancers are highly lethal cancers that require precise prediction in clinical practice. Serum ferritin level increases in malignancy and high serum ferritin level is associated with poor survival in various cancers. This study aimed to identify whether serum ferritin could independently predict the overall survival (OS) of patients with advanced hepatobiliary cancers.MethodsThe retrospective cohort study was performed by reviewing medical records of patients with advanced hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Upregulation of ferritin has been shown to correlate with poor prognosis in several cancers, including HNSC, non-small cell lung cancer, and liver cancer [ 24 , 25 ]. Nevertheless, apart from two studies showing that FTL is elevated in GBM and colorectal cancer [ 26 , 27 ], little is known about the expressions of FTL and FTH1 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of ferritin has been shown to correlate with poor prognosis in several cancers, including HNSC, non-small cell lung cancer, and liver cancer [ 24 , 25 ]. Nevertheless, apart from two studies showing that FTL is elevated in GBM and colorectal cancer [ 26 , 27 ], little is known about the expressions of FTL and FTH1 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 38 ] Albumin is an important indicator reflecting the patients’ nutritional status and has been used for prognostic assessment of patients with ovarian cancer, advanced hepatobiliary cancer, and NPC. [ 16 , 39 , 40 ] The CAR was initially used to assess the outcome of patients with acute medical admissions and sepsis. [ 41 , 42 ] Moreover, previous studies have demonstrated that CAR is superior prognostically for various cancers than are the established inflammation-based prognostic indices Glasgow prognostic score (GPS), modified GPS, and prognostic nutritional index.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin is an iron-containing protein with multiple functions in iron delivery, cell proliferation, angiogenesis, and immunosuppression. Under the case of cancer, ferritin is detected in high concentration in plasma in many patients, and its higher level correlates with higher clinical tumor stage and poorer patients’ outcome [23,24]. Iron–sulfur biogenesis is another common form of iron utilization.…”
Section: Regulation Of Iron Homeostasis In Cancermentioning
confidence: 99%